Dadra and Nagar Haveli Draft Annual Plan 1994-95 - Planning Commission (Planning Commission, 1994)
Dadra and Nagar Haveli became a separate Union Territory (UT) in 1961 after it was merged with Union of India from Free Administration of Dadra and Nagar Haveli formed by the people themselves in 1954 after liberation from 450 years colonial rule of Portugal. Inspire of being a U.T. efforts have been made to improve resource mobilisation by efficient endorsement of taxes permitted to be levied by Govt. of India.
Union Territory of Dadra and Nagar Haveli, Department of Planning and Statistics, U.T. Administration of Daman and Diu